The Effect of Using Flash Card Media on the Reading Ability of Grade II Students at SD Muhammadiyah 13 Medan Academic Year 2024/2025. - Yunita Ulfa Munthe; Amin Basri (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2025)
This study aims to determine the effect of using flash card media on students’ reading ability in the Indonesian language subject, specifically on verb material, in Grade II at SD Muhammadiyah 13 Medan. This study employed a descriptive quantitative research design. The sample in this study consisted of Grade II A students as the experimental class totaling 21 students and Grade II B students as the control class totaling 16 students. Data collection techniques were conducted through tests and observation sheets. The population of this study included all Grade II students at SD Muhammadiyah 13 Medan. Meanwhile, the data analysis technique used was the t-test.The results of the study showed that the reading ability of Grade II students in the control class improved from a pre-test score of 38.5 to 71.4 in the post-test. The reading ability of students in the experimental class experienced a significant improvement after the implementation of flash card media, from an average pre-test score of 49.3 to 78.75 in the post-test. This indicates that flash card media are effective in improving students’ reading ability.Based on data analysis using the t-test and the hypothesis testing results, the obtained significance value (sig. 2-tailed) was 0.004. Therefore, the significance value of 0.004 < 0.05 indicates a significant difference, meaning that the working hypothesis (Ha) in this study was accepted. Thus, it can be concluded that there is an effect of the use of flash card media on the reading ability of Grade II students at SD Muhammadiyah 13 Medan.